MAQAṢID AL-SYARIAH IN FATWA YUSUF AL-QARDHAWI ABOUT MISYAR MARRIAGE - Jumria P; Faisal Faisal; Husnul Yaqin (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2023)
The existence of misyar marriage does not aim to build sakinah, mawaddah and rahmah households. Meanwhile, according to Yusuf al-Qardhawi in his fatwa, it is permissible as long as it is in an urgent condition. So the author looks at it from the point of view of his Maqasid al-Shariah. Research Methods In this study using a qualitative descriptive approach. Protection of the Soul/Body (Hifz al-Nafs). Scholars who allow misyar marriage are of the opinion that when viewed from the realization of the great goals of a marriage, it is true that misyar marriage is not an ideal form of marriage. Property Protection (Hifz al-mal). With misyar marriage, a rich wife can help her husband's economy which may be weak. This is in line with the concept of maqaṣid al-shariah in the realm of al-nafs at the tahsiniyat level. Apart from that, with a misyar marriage, the wife is lucky because she has someone who can protect herself and her property from damage and interference from other parties. Protection of the Intellect (Hifz al-Aqli). Forms of human care for the mind and thoughts by living a healthy way and continuing to develop their natural talents. Protection of Offspring (Hifz al-Nasl). The initial purpose of marriage is so that husband and wife can live together forever, day and night in order to achieve a life that is sakinah, mawaddah, wa rahmah.